PENGKAJIAN BIONOMIK NYAMUK ANOPHELES SEBAGAI PENDEKATAN UNTUK MENGENDALIKAN POPULASINYA DALAM UPAYA MENANGGULANGI MALARIA (Studi kasus di Desa Kalibening, Kecamatan Sukoharjo, Kabupaten Wonosobo, Provinsi Jawa Tengah) - Bina Ikawati; Dewi Marbawati (Balai Penelitian dan Pengembangan Kesehatan Banjarnegara Badan Litbangkes Kemenkes RI, 2008)
A study on Bionomic of Anopheles mosquitoes as an approach to control the population of malaria (case studyat Kalibening Village, Sukoharjo Subdistrict, Wonosobo Regency, Central Java) had been conducted in July-October 2006. The objective of the study is to identify the bionomic of malaria vector. The result of this study revealed five species of Anopheles such as An. maculatus, An barbirostris, An. balabacensis, An. aconitus dan An. vagus. Three of them (An. aconitus, An. maculatus, An. balabacensis) represent as malarias vector in Java. Unfortunately these results were not supported by the ELISA test, since it proved that they are proven to be negative malaria vector. An. maculatus was found predominantly. The parous rate of An. maculatus was 39,89% (77 mortalities out of 193). Mosquoito age of An. maculatus ranged from 0.25-2.35 days. Thus, they were hardly to be a vectors. However, the situation might be different, under some circumstances, e.g. seasonal change. On the other way around, An. balabacensis and An. maculatus had a high density. An. Maculatus were mostly found in the ground pool around Salak plantation. Their bitting graphics (located at in door and out door) always occured at the same time. High in July then slowing down in Agust up to September and increased again in October whether those which were located in the cage were low in July, increasing in August up to September and slowing down in October. The peak density of An. maculatus which was biting on man occured at mid night (00. 00- 01. 00) and early in the morning (04. 00-05. 00) outdoors and indoors respectively.